Risk factors for postoperative complications after pheochromocytoma and/or paraganglioma: a single-center retrospective study - Ma, Lulu; Yu, Xuerong; Huang, Yuguang (Frontiers in Oncology, 2023)
Background Perioperative complications are higher in patients with pheochromocytoma and/or paraganglioma. The aim of this study was to identify the risk factors of postoperative complications after pheochromocytoma and/or paraganglioma resection surgery. Method We retrospectively reviewed 438 patients who underwent laparoscopic or open surgery for pheochromocytoma and/or paraganglioma at our center between January 2014 and December 2019. Demographic characteristics and intraoperative and postoperative data were recorded. Complications were defined as deviations from the normal postoperative course and Clavien–Dindo classification was used to grade the severity of postoperative complication. Patients with complications of grade II or above were included for analysis. Binary logistic regression was used to determine the risk factors for postoperative complications. Results The median age of the patients was 47 years old. There were 295 cases (67.4%) of phepchromocytoma and 143 cases (32.6%) of paraganglioma. Three hundred sixty-seven (87.8%) patients had laparoscopic approach, and 55 (12.6%) patients had laparotomy; the conversion rate from laparoscopy to laparotomy was 3.7%. Eighty-seven complications occurred in 65 patients (14.8%). No death occurred in our study and transfusion (36, 8.2%) was the most common complication. The mean follow-up length was 14 months. Independent risk factors for postoperative complications included a tumor size larger than 5.6 cm (OR = 2.427, 95% CI 1.284–4.587, P = 0.006), laparotomy (OR 2.590, 95% CI 1.230–5.453, P = 0.012), conversion to laparotomy (OR = 8.384, 95% CI 2.247–31.285, P = 0.002), and the operation time longer than 188 min (OR = 3.709, 95% CI 1.847–7.450, P < 0.001). Conclusion Complications were not uncommon after pheochromocytoma and/or paraganglioma surgery. Tumor size, surgical type, and operation time were determined as the risk factors for postoperative complications. These factors should be considered to improve perioperative management.